Examining the National Security Strategy in Cooperation between Indonesia and the United Arab Emirates in the Defense Sector - Aulia, Mufida Inas; Samputra, Palupi Lindiasari; Machmudi, Yon (Universitas Muhammadiyah Gorontalo, 2024)
Indonesia and the United Arab Emirates (UAE) have established close ties, including cooperation in the defense sector. The development of global trends has made national security issues the axis of interest in every country. National security is not only related to military threats, but includes various aspects such as economic, political, social and cultural. Indonesia and the United Arab Emirates (UAE) are two countries that have close relations by collaborating in various fields, one of which is in the defense sector. Based on Buzan's securitization theory, identity conflict, regional hegemony, and the threat of terrorism are included as threats to the components of national security, namely the idea of the state, the physical basis of the state, and the institutional expression of the state. Researchers use systematic reviews as a method in research which is also used to determine research gaps. This study uses search engines such as Taylor & Francis Online, JSTOR, Tandfonline, ProQuest, and Google Scholar to search for various credible sources in the form of journals, articles, and empirical studies. The author finds that identity conflict, regional hegemony, and the threat of terrorism are threat factors that influence national security. So, the change in the status of defense industry cooperation from Business-to-Business (B2B) to Government-to-Government (G2G) appears as an interesting issue to analyze the factors and impacts.